Can we get back to full employment ? / by Maurice Scott and Robert A.Laslett - "Scott,Maurice" (London, 1978)
In this book the author examine the various explanations of continuing and increasing unemployment. It is said that, for many low-paid workers, there is little financial inducement to work once allowance is made for income taxon earning and the tax free benifits received by the unemployed.
Keywords: Unemployment